2013
DOI: 10.1177/1548512913502880
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness testing of non-lethal weapons

Abstract: Non-lethal weapons (NLWs) provide the warfighter with tools to effectively wage full spectrum operations, particularly in counterinsurgency, stability and support, and peace operations. However, it is widely recognized that evaluation of a NLW's performance and effectiveness is problematic. The principal difficulty is that a NLW must be evaluated as both a non-lethal device (based on clinical testing methods of life science) and as a weapon (based on US Department of Defense (DoD) evaluation and testing method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…12 Given the promises that LVC presents to training and the research challenges that have been identified, the Journal of Defense Modeling and Simulation published a special issue devoted to the ''Art and Science of Live, Virtual and Constructive Simulation and Intelligent Agents to Support Defense and Homeland Security Testing and Analysis''. 13 In the issue, the examples of the use of LVC span a wide range of topics and application areas, e.g., the challenges that are met when using LVC simulation for test and evaluation purposes 4 , the testing of non-lethal weapons in an LVC setting, 14 and challenges with attaining sufficient realism in the results of LVC simulations. 4 More recently, Mansikka et al presented and demonstrated a comprehensive LVC framework for development of air combat tactics, techniques, and procedures (TTP).…”
Section: Lvc Researchmentioning
confidence: 99%
“…12 Given the promises that LVC presents to training and the research challenges that have been identified, the Journal of Defense Modeling and Simulation published a special issue devoted to the ''Art and Science of Live, Virtual and Constructive Simulation and Intelligent Agents to Support Defense and Homeland Security Testing and Analysis''. 13 In the issue, the examples of the use of LVC span a wide range of topics and application areas, e.g., the challenges that are met when using LVC simulation for test and evaluation purposes 4 , the testing of non-lethal weapons in an LVC setting, 14 and challenges with attaining sufficient realism in the results of LVC simulations. 4 More recently, Mansikka et al presented and demonstrated a comprehensive LVC framework for development of air combat tactics, techniques, and procedures (TTP).…”
Section: Lvc Researchmentioning
confidence: 99%
“…However, the psychological effects of NLW use are less clear and more variable. To date, the psychological research that has been conducted is based mostly on crowd and riot populations (Bliss, 2004;Mezzacappa 2014). For example, Mezzacappa (2014) has organized crowd simulations to further understand the emotional and cognitive processes involved in NLW use and its effects.…”
Section: Non-lethal Weapon Use and Peacekeepingmentioning
confidence: 99%
“…For example, Mezzacappa (2014) has organized crowd simulations to further understand the emotional and cognitive processes involved in NLW use and its effects. Non-lethal weapon use shows evidence of crowds being controlled, crowd members remaining in place, crowds being more hesitant in approaching law enforcement officials, and crowds spending less time in the line of fire near off limit areas (Mezzacappa, 2014).…”
Section: Non-lethal Weapon Use and Peacekeepingmentioning
confidence: 99%
See 1 more Smart Citation
“…LVC involves live people role playing with a live instructor (live), live people interacting with simulated entities (virtual), or simulated entities interacting with one another in a simulated environment (constructive). The use of LVC in the military domain has been the subset of a special issue in JDMS and the approach has been shown to be useful in testing and analysis, 15,16 training, 17 verification, 18 and modeling counter-insurgency. 19 The key assumption, when considering LVC as a viable form for designing and using SoS, is that the interactions between the live, virtual, and constructive components may account for the human/social aspect of SoS.…”
Section: Introductionmentioning
confidence: 99%